Jewish Ethics in a Post-Madoff World - Pava, M. author. aut Link
XVII, 206 p.
Keywords: Moses Pava explores new and alternative ways of relating to Jewish texts and concepts. In doing so, he invents a nuanced, flexible, and sufficiently sensitive vocabulary to conduct productive ethical dialogues, both within and between communities.